ANALISIS PENGARUH KOMPOSISI DEWAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN DI INDONESIA (Studi pada Bank Umum yang Listing di Bursa Efek Indonesia Tahun 2016-2020) - Fatima, Dahniar Fara; Hersugondo, Hersugondo (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
This study aims to examine the effect of the composition of the board consisting of Board Size, Board of Directors, Non-Affiliate Directors, Board of Commissioners, Independent Commissioners, and Audit Committee on profitability (ROA) of banking companies listed on the IDX in 2016-2020. The problem of this research is caused by the existence of a research gap from previous studies. In this study, the sample was taken by adopting a purposive sampling method, a sample of 38 sector companies. This research uses secondary data which is downloaded from the official website of Bloomberg. The analytical method adopted for the research hypothesis is multiple linear regression. From the results of data processing, the research shows that BDSIZE, DCOMM, and INDCOMM have a significant effect on the profitability (ROA) of the banks listed on the IDX. DDIRECT, NONAFFDIRECT, AUDIT have no significant effect on the ROA of the banks listed on the IDX.